Prevalence and factors associated with depressive, anxiety and stress symptoms among women with gestational diabetes mellitus in tertiary care centres in Malaysia: a cross-sectional study - Kai Wei Lee; Siew Mooi Ching; Fan Kee Hoo; Vasudevan Ramachandran; Seng Choi Chong; Maiza Tusimin; Noraihan Mohd Nordin (BMC, 2019)
Abstract Background Research on antenatal depressive, anxiety and stress symptoms among women with gestational diabetes mellitus (GDM) is lacking in Malaysia. This study aimed to determine the prevalence and factors associated with antenatal depressive, anxiety and stress symptoms among Malaysian women with GDM. Methods This was a descriptive, cross-sectional study of 526 women with GDM. Depressive, anxiety and stress symptoms are defined as the final score in mild to extremely severe risk in the severity rating scale. Data analysis was performed using SPSS v.21, while multiple logistic regression was used to identify predictors of depressive, anxiety and stress symptoms. Results Prevalence of anxiety symptoms was highest (39.9%), followed by depressive symptoms (12.5%) and stress symptoms (10.6%) among women with GDM. According to multiple logistic regression analyses, younger age (OR = 0.955, 95% CI = 0.919-0.993), comorbidity with asthma (OR = 2.436, 95% CI = 1.219-4.870) and a family history of depression and anxiety (OR = 4.782, 95% CI = 1.281-17.853) had significant associations with antenatal anxiety symptoms. Being non-Muslim (OR = 2.937, 95% CI = 1.434-6.018) and having a family history of depression and anxiety (OR = 4.706, 95% CI = 1.362-16.254) had significant associations with antenatal depressive symptoms. Furthermore, being non-Muslim (OR = 2.451, 95% CI = 1.273-4.718) had a significant association with antenatal stress symptoms. Conclusions Within a population of women with GDM in Malaysia, those at higher risk of having depressive, anxiety and stress symptoms can be identified from several baseline clinical characteristics. Clinicians should be more alert so that the high-risk patients can be referred earlier for further intervention.